Phytoremediation of Soil Contaminated with Lead and Cadmium Metals - Abdullaev, Faziljon Tursunovich; Eshboboev, Turaqul Usmanovich (American Journal of Botany and Bioengineering, 2024)
Soil contamination with heavy metals such as lead (Pb) and cadmium (Cd) poses severe risks to human health, agriculture, and ecosystems. Phytoremediation, an eco-friendly and cost-effective technology, has emerged as a sustainable solution for decontaminating such polluted soils. This study explores the mechanisms and effectiveness of phytoremediation in reducing Pb and Cd concentrations in soil using hyperaccumulator plant species. Key processes, including phytoextraction, phytostabilization, and rhizofiltration, are discussed. The study also highlights factors affecting the efficiency of phytoremediation, such as plant species selection, soil properties, and the bioavailability of metals. Results indicate that certain plants significantly reduce Pb and Cd levels in soil, offering a practical approach to mitigate heavy metal pollution and restore soil health.